Pengembangan Media Pembelajaran Powerpoint Interaktif Pada Materi Sistem Pencernaan Manusia Kelas V SDN 011 Lenggadai Hulu Kabupaten Rokan Hilir - Sundari, Sundari; Fitriyeni, Fitriyeni (Cetta: Jurnal Ilmu Pendidikan, 2025)
One of the efforts that can be made to make the learning process more engaging and meaningful is through the use of instructional media such as PowerPoint. This study aims to develop interactive PowerPoint-based learning media for fifth-grade science material with the topic "The Human Digestive System" at SDN 011 Lenggadai Hulu. The background of this research stems from interviews with teachers, which revealed that the teaching process is still conventional and has not utilized engaging media, resulting in low student interest and participation. The study employed a Research and Development (R&D) method using the ADDIE model but was only carried out up to the development stage. Data were collected through observation, interviews, and validation by media and content experts. The validation results indicate that the developed interactive PowerPoint media is highly suitable for use in learning, in terms of content, visual design, and ease of use. This media is expected to serve as an innovative solution to enhance the effectiveness and student engagement in science learning, as well as to instill environmental awareness from an early age.